The role of sodium-based additives on reduction process of nickel lateritic ore. (February 2019) - Nurjaman, F; Rahmahwati, A; Karimy, M F; Hastriana, N; Shofi, A; Herlina, U; Suharno, B; Ferdian, D
Abstract: In this present work, the selective reduction of nickel laterite was conducted by using 5 to 15 wt. % of sodium carbonate, sodium chloride and sodium sulfate as additives. The 5% wt. of palm shell charcoal was used as the reductant. The selective reduction process for nickel laterite was carried out at 1150°C for 60 minutes followed by wet magnetic separation using 500 Gausses permanent magnet. The characterization of reduced ore was performed by using X-ray Diffraction, optical microscope and Scanning Electron Microscope with Energy Dispersive X-ray Spectroscopy, while the chemical composition of concentrate or ferronickel was identified by X-ray Fluorescence. The results showed that the increase of nickel grade and recovery of nickel laterite was significantly more affected by the addition of sodium sulfate rather than sodium carbonate and sodium chloride. The ferronickel particle was agglomerated and growth with the increasing of reduction temperature and dosses of additives, thus it provided favorable conditions for the separation of ferronickel from impurities in the magnetic separation process.